Pengaruh Campuran Feses Sapi Potong dan Feses Kuda Pada Proses Pengomposan Terhadap Kualitas Kompos - Hidayati, Yuli Astuti; Marlina, Eulis Tanti; Benito AK, Tb; Harlia, Ellin (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
This  study  aims  to  determine  compost  quality  (content  of   N,  P2O5, K2O)  generated  from  various mixtures  of  beef  cattle  feces  and  the  feces  of  horses.  The method    used    in  this  study  is  the  experimental method in the laboratory using a completely randomized design with 3 treatments, ie P1 = C / N ratio of 25, P2  =  C  / N  ratio  of  30  and  P3  =  C  / N  ratio  of  35  and  replications  6  times.  To  determine  the  effect  of treatments, data were analyzed with ANOVA and Duncan test. The results showed that the mixture of feces of beef  cattle and horse  feces with various C  / N  ratio did not  significantly affect  the quality of  compost. N content  in  compost  produced =  0.7867  to  0.8000%, P2O5  content =  0.5883  to  0.6000%, K2O =  0.5733  to 0.5883%